Synthesis, characterization and properties of poly(butanediol sebacate–butanediol terephthalate) (PBSeT) copolyesters using glycerol as cross-linking agent. (September 2021) - Li, Zhimao; Li, Yingchun; Dong, Xing; Wang, Wensheng; Zhu, Yong-Chuang; Murugadoss, Vignesh; Song, Gang; Naik, Nithesh; Pan, Duo; Guo, Zhanhu
Abstract: High molecular weight aliphatic-aromatic copolyesters were synthesized from Sebacic acid, terephthalic acid, 1, 4-butanediol and glycerol via two-step esterification and polycondensation. Copolyesters were characterized with intrinsic viscosity, gel permeation chromatography, X-ray diffraction, Fourier infrared spectroscopy, nuclear magnetic resonance, differential scanning calorimetry, thermogravimetric analysis, rheological analysis, tensile and puncture testing. All the copolyesters had a weight-average molecular weight over 20, 000 g/mol or intrinsic viscosity over 1.1 dL/g when the glycerol content was in the range from 0.04 to 0.1 mol. Particularly, in addition to a small reduction in the tensile strength and elongation at break, the molecular weight, crystallinity, and intrinsic viscosity of the polyester were increased when the glycerol content was 0.04 mol, and the puncture resistance reached its maximum, which would improve the performance of the copolyester film. Obviously, the addition of glycerol did not significantly affect the melting temperature, glass transition temperature and thermal stability of polyesters, which would make it possible to use copolyester as a base material for cold-resistant hydrogels. As a whole, the level of glycerol within 0.1 mol is sufficient to improve the properties of copolyesters, which is beneficial to promote the generalization of them for films and hydrogels. Highlights: Perforation-resistant poly(butanediol sebacate–butanediol terephthalate) (PBSeT) copolyesters were synthesized by adding glycerol (GL). The reaction time of polycondensation was shortened as a result of GL. The puncture resistance of PBSeT was clearly improved due to the addition of GL.